CHARACTER BUILDING IN THE PERSPECTIVE OF PANCASILA: A CASE STUDY OF ISLAMIC RELIGIOUS EDUCATION STUDENTS - Ladamay, Ode Mohamad Man Arfa; Mustakim, Mustakim (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2023)
The values of character building in students are a reflection of the institution in preparing future generations who have religious, tolerant, democratic and love the country’s characters. The purpose of this study is to describe character building for students, and the implementation of character building in the perspective of Pancasila. This research uses a qualitative method with a case study type of research. The results of the study illustrate that: (1) character building in students is seen in student discipline when attending lectures offline and online. In addition, student creativity when attending lectures is getting better with creative ideas, high curiosity leads students to have an attitude to ask questions and provide arguments in accordance with the experiences students have. character building for students is also seen in the responsibilities of students in submitting assignments for Pancasila Education courses in a timely manner; and (2) the implementation of character building in accordance with the perspective of Pancasila is manifested in the core values of Pancasila which are internalized in the first precept character building reflected in the behaviour of diligent worship, and tolerance between religious communities; the second precept is reflected in polite behaviour, mutual respect, and as an example; the third precept which is manifested through a sense of unity and oneness, a spirit of self-sacrifice, and love for the motherland; the fourth precept through the embodiment of always respecting the opinions of others, prioritizing deliberation for consensus, and upholding democracy; and the fifth precept through fairness in opinion, mutual welfare, and always respecting each other's self-actualization.